PENERAPAN SANKSI PENGEBOMAN IKAN MENURUT UNDANG-UNDANG NO. 45 TAHUN 2009 TENTANG PERIKANAN DI PERAIRAN HALMAHERA UTARA - Dyah Retno Puspitasari (JPSI (Journal of Public Sector Innovations), 2019)
Catching fish with fish bombs is against the law, in accordance with the regulations on legal sanctions for fish bombings stated in Law No. 45 of 2009 concerning Amendments to Law No. 31 of 2004 concerning Fisheries, in Article 85 fish catchers who damage the sustainability of fish resources in the NKRI fishery region can be sentenced to a maximum of five years in prison and a maximum fine of two billion rupiah. The research objective was to determine the inhibiting factors of the application of fish bombing sanctions according to the Fisheries Act in North Halmahera waters. The method used in this study is normative juridical research, with a statutory approach. The inhibiting factors are the lack of legal awareness of the fishermen community, due to economic factors - to improve the welfare of fishermen, as well as the lack of patrol boats for supervision in the Halut waters by the Halut Water Police Unit, so there is a need for coordination among institutions other than Sat Polair Halut, namely the Marine Service and Fisheries, also the community itself.